Prediction of Myocardial Infarction From Patient Features With Machine Learning - Chen, Zhihao; Shi, Jixi; Pommier, Thibaut; Cottin, Yves; Salomon, Michel; Decourselle, Thomas; Lalande, Alain; Couturier, Raphaël (Frontiers in Cardiovascular Medicine, 2022)
This work proposes machine learning-based models to automatically evaluate the severity of a myocardial infarction (MI) from physiological, clinical and paraclinical features. Two types of machine learning models are investigated for the MI assessment: the classification models classify the presence of the infarct and the persistent microvascular obstruction (PMO), and the regression models quantify the Percentage of Infarcted Myocardium (PIM) of patients suspected of having an acute MI during their reception in the emergency department. The ground truth labels for these supervised models are derived from the corresponding Delayed Enhancement MRI (DE-MRI) exams and manual annotations of the myocardium and scar tissues. Experiments were conducted on 150 cases and evaluated with cross-validation. Results showed that for the MI (PMO inclusive) and the PMO (infarct exclusive), the best models obtained respectively a mean error of 0.056 and 0.012 for the quantification, and 88.67% and 77.33% for the classification accuracy of the state of the myocardium. The study of the features' importance also revealed that the troponin value had the strongest correlation to the severity of the MI among the 12 selected features. For the proposal's translational perspective, in cardiac emergencies, qualitative and quantitative analysis can be obtained prior to the achievement of MRI by relying only on conventional tests and patient features, thus providing an objective reference for further treatment by physicians.